Perkembangan Hukum Administrasi Negara di Indonesia (Jurnal Begawan Hukum (JBH), 2024)
In general, regarding administration and its construction, it brings us to the administrative reality which is the basis for the government to carry out and exercise its authority. Law is the main basis for living life. Guarantee the principles of order and discipline so that order can be implemented. Guarantee a sense of freedom, security, comfort and order. In general, there is no point in including obligations or prohibitions for citizens in state administrative laws and regulations.